Sistem Pendukung Keputusan Pemilihan Kepala Keperawatan Menggunakan Metode MABAC - Rusman Waruwu (ADA Research Center, 2024)
The head of nursing is a profession or position in charge of leading and being fully responsible for controlling and organizing all nursing service activities in the hospital, by organizing and structuring nursing activities so that the head of nursing has an important task in coordinating his subordinates. In the selection of the head of nursing is very complicated because it requires the requirements that must be met in the selection of the head of nursing, the criteria that must be met include education, attitude, tenure, performance and others. Currently, the system used for selecting the head of nursing still uses a manual method by receiving input from other members of the nurses and assisted by the director or head of the hospital itself. The MABAC method is a multicriteria comparison method, this method the author chose because this method provides a consistent solution and is also very reliable in decision making compared to other methods in the process of selecting the head of nursing. Based on the calculations that have been carried out, the one who deserves to be appointed as the head of Nursing at Estomihi Hospital with a value of 0.68413 is Asfriani Simanullang (Alternative code A2).